Financial Analysis for Five Drilling Rigs Investment to Serve Pertamina Market Through Joint Operation PTDU and PDSI (The Indonesian Journal of Business Administration, 2012)
Indonesia in one of the largest oil producers in the world, its potential oil resources is stored beneath the belly of the earth of Indonesia; some are proven oil reserves but some still potential oil reserves. PERTAMINA as a state owned company have responsibilities to manage oil business industry in Indonesia, their country’s potential oil resources need to be managed including oil exploration, oil drilling, oil refinery and any other process until the natural resources is ready to supply oil demand in all over the world. Scope of discussion of this research is limited into a narrower scope of oil drilling. PDSI (PT PERTAMINA Drilling Services Indonesia) is one of PERTAMINA’s subsidiaries that operate in drilling rig business; PDSI also carrying same responsibilities like its parent company. PTDU (PT Dimas Utama) saw an opportunity to do joint operation with PDSI, because PTDU have resources of drilling rigs from Chinese investor. PTDU become like a bridge between Chinese Investor and PDSI, but the business scheme needs a financial engineering because Chinese investor wants a 200% return in year five which is normally made for more than five years. Therefore feasibility study is needed for this business scheme, decision tree analysis also used because there are possibilities and decisions on the business scheme. The results of the feasibility study are feasible IRR (Internal Rate of Return), ROI (Return on Investment), ROE (Return on Equity), PP (Payback Period), and NPV (Net Present Value), so PTDU should take this investment project. Keywords: drilling rig, financial analysis, PERTAMINA, PDSI, drilling services